Default- and call-adjusted duration for corporate bonds - Jacoby, Gady; Roberts, Gordon S. (Journal of Banking & Finance, 2003)
Call and default can potentially alter the timing and amounts of promised cashflows for callable, corporate bonds. While prior research has indicated the theoretical importance of adjusting Macaulay duration for the impacts of default and call, the question of their relative impact remains a matter of debate [The High Yield Debt Market, Dow Jones Irwin, New York, 1990, p. 18; J. Finan. 53 (1998) 2225]. We develop a theoretical analysis incorporating both default and call effects on duration and test its implications employing a previously unexplored data base of Canadian, investment grade, corporate bond indices containing an unusual provision making it possible to identify callable and noncallable indices.